Species Diversity, Phylogeny, Divergence Time, and Biogeography of the Genus Sanghuangporus (Basidiomycota) - Zhu, Lin; Song, Jie; Zhou, Jun-Liang; Si, Jing; Cui, Bao-Kai (Frontiers in Microbiology, 2019)
“Sanghuang” is a popular fungus used as a Chinese traditional medicine. In fact, it represents a group of fungi belonging to the genus Sanghuangporus, but little is known about its origin and biogeography. The aim of this study was to characterize the molecular relationships, origin and biogeographical distribution of Sanghuangporus. The multi-locus phylogenetic analyses were used to infer the phylogenetic relationships. In addition, based on Bayesian evolutionary analysis using sequences from the internal transcribed spacer (ITS), nuclear large subunit rDNA (nLSU), translation elongation factor 1-α (EF1-α), and the largest and second largest subunits of RNA polymerase II (RPB1 and RPB2), we used a fungus fossil-based approach to gain insight into the divergence time of species in Sanghuangporus. The molecular phylogeny strongly supports the monophyly of Sanghuangporus (MP = 100%, ML = 100%, and BPP = 1.00), and 13 species are recognized in this genus. The Bayesian uncorrelated lognormal relaxed molecular clock using BEAST and reconstructed ancestral areas indicate that the maximum crown age of Sanghuangporus is approximately 30.85 million years. East Asia is the likely ancestral area (38%). Dispersal and differentiation to other continents then occurred during the late Middle Miocene and Pliocene. The ancestor of Sanghuangporus probably originated in palaeotropical Northeast Asia and covered Northeast Asia and East Africa during the Oligocene-Miocene, hosted by plants that expanded via the “Gomphotherium Landbridge.” Six kinds of dispersal routes are proposed, including intercontinental dispersal events of three clades between Northeast Asia and East Africa, between East Asia and North America, and between Northeast Asia and Europe.